2009
DOI: 10.3168/jds.2008-0990
|View full text |Cite
|
Sign up to set email alerts
|

Yeast culture supplementation prevented milk fat depression by a short-term dietary challenge with fermentable starch

Abstract: Effects of yeast culture on responses to a fermentable starch challenge were evaluated in an experiment with a crossover arrangement of treatments for yeast culture supplementation with 28-d periods and a fermentable starch challenge on the last 2 d of each 28-d period as a split plot within period. Eight ruminally cannulated, midlactation, multiparous Holstein cows (96 +/- 14 d in milk) were randomly assigned to treatment sequence. Treatments were yeast culture or control (mix of dry ground corn and soybean m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 35 publications
4
40
3
Order By: Relevance
“…However, in the current study although lower ammonia concentrations that may be associated with, increased bacteria activity by some y e a s t s cultures, no modifications of pH of the medium and increase in degradation of dry matter were found. Lack of effect of yeast products on rumen pH and degradation of dry matter is consistent with recent reports in lactating dairy cows (Longuski et al, 2009). have the capability of stimulating rumen function.…”
Section: Resultssupporting
confidence: 80%
“…However, in the current study although lower ammonia concentrations that may be associated with, increased bacteria activity by some y e a s t s cultures, no modifications of pH of the medium and increase in degradation of dry matter were found. Lack of effect of yeast products on rumen pH and degradation of dry matter is consistent with recent reports in lactating dairy cows (Longuski et al, 2009). have the capability of stimulating rumen function.…”
Section: Resultssupporting
confidence: 80%
“…This dietary profile may have contributed to the responses registered to yeast supplementation. Actually, diets capable of increasing rumen environment acidity may favor the response potential to yeast supplementation (Williams et al, 1991;Longuski et al (2009).…”
Section: Resultsmentioning
confidence: 99%
“…Longuski et al (2009) reported a negative effect of yeast on the rumination activity of dairy cows, which can suggest that fiber digestibility responds positively to the yeast supplementation. However, similar phenomenon was not recorded in the present study (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Yeasts, in particular different strains or commercial products of Saccharomyces cerevisiae, have been tested on dairy cows with a number of positive effects such as increased dry matter intake (DMI) and milk production (Wohlt et al,1998;Dann et al, 2000); improved diet digestibility (Erasmus et al, 1992;Marden et al, 2008); stabilized rumen pH (Bach et al, 2007); and stimulated rumen bacteria growth (Newbold et al, 1995). However, there are also many studies with no or negative responses to yeast supplementation (Mwenya et al, 2005;Longuski et al, 2009;Chung et al, 2011), probably related to the strong influence of the basal diet, the variation in yeast strains and the different commercial formulations.…”
Section: Introductionmentioning
confidence: 99%